Reconceptualising early language development: matter, sensation and the more-than-human. Issue 6 (2nd November 2021) - Hackett, Abigail; MacLure, Maggie; McMahon, Sarah
ABSTRACT: This article critically interrogates the model of language that underpins early years policy and pedagogy. Our arguments emerge from an ethnographic study involving 2-year-olds attending a day care centre that had begun to hold a substantial proportion of its sessions outdoors. The resultant shift in pedagogy coincided with changes in the children's speaking and listening practices. We take these changes as a starting point for a reconceptualisation of early language and the conditions under which it develops. Drawing on posthuman and Deleuzian theory, we propose a relational- material model of early language, which situates language within a wider, multi-sensory and more-than-human milieu, in which children are immersed from their earliest days. We end by asking whether early language development might be better supported by paying less attention to words, grammar and meaning, in favour of fostering participation in dynamic, multisensory, collective events.